Source apportionment of ambient concentration and population exposure to elemental carbon in South Korea using a three-dimensional air quality model - Son, Kyuwon; Kim, Byeong Uk; Kim, Hyun Cheol; Kim, Soontae (Air Quality, Atmosphere and Health, 2022)
We quantified the foreign and domestic contributions to annual mean elemental carbon (EC) concentration over South Korea in 2016 using the Primary Carbon Appointment tool in the community multiscale air quality model. The individual domestic contributions were further examined by emission source category (area, mobile, and point) in each sub-region (i.e., Seoul Metropolitan Area (SMA), Gangwon, Chungcheong, Youngnam, and Honam). EC contribution and population-weighted exposure contribution (PWEC) for each emission source were calculated. Two indicators were compared and adjusted considering uncertainties of emissions from sub-regions. Based on the results of this analysis, the primary EC emission sources that need to be managed to alleviate the concentrations and PWECs were classified, and the cost-effectiveness was compared with contribution rates for EC and PWEC. The modeled annual mean EC concentration in South Korea was 0.6 µg/m3, of which 54% was contributed by foreign sources (0.3 µg/m3). However, the quarterly foreign contribution differed by up to five times depending on the monsoon, while the domestic contribution did not. Simultaneously, spatial variations of the annual mean EC contributions are smaller than those of the foreign contributions. Regardless of the uncertainty of emissions, domestic PWEC was 20% higher than the domestic concentration as domestic EC emissions were concentrated in densely populated areas. It implies that EC emission control has more significant meaning not only to improve concentration but also to improve population exposure. In addition, the contribution rate showed greater variation between sub-regions than the EC emission source categories within a region. Considering this, if the cost used to reduce a unit EC emission is the same, the cost effect can be expected when EC emissions are reduced in the sub-regions with a large contribution rate regardless of EC emission source category.
Keywords: Contribution; EC; Population exposure; Source–receptor; Transport